Changes in morphology of the lateral abdominal wall muscles during sagittal tilting in young healthy subjects - Białach, Małgorzata; Bugdol, Monika; Bibrowicz, Karol; Myśliwiec, Andrzej (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2024)
Introduction. The lateral abdominal wall muscles and their recruitment are the subjects of common interest for researchers due to their clinical importance and practical application in athletes and non-athletes. So far, no repeatable method aimed at activating speciﬁc muscles by passive tilting has been discovered. In this paper, changes in the morphology of muscles of the lateral abdominal wall during passive body inclinations in the sagittal plane in a standing position were assessed. The objec-tive was to determine whether a device with the mentioned function would be able to induce reﬂex activation of the trunk stabilisers and can be used in an initial stage of postural rehabilitation and re-education.Methods. A total of 179 healthy subjects aged 18–30 (96 women and 83 men) participated in the study. They were divided into groups according to the body mass index and the value of the pelvic tilt in the sagittal plane. The subject’s body (in a standing, habitual position in a specially developed device) was tilted in steps, every 1 angular degree, each time taking ultrasound measurements of the muscle thickness on the right side, starting from the vertical to a maximum value of 7 degrees. The cross-section of the external oblique, internal oblique, and transverse abdominal muscles was measured.Results. Each of the three muscles changed its thickness in a statistically signiﬁcant way accidentally at diﬀerent degrees of inclination, thus not showing a homogeneous contraction pattern.Conclusions. There are no indications for clinical application of the forward sagittal inclination in accordance with the imple-mented procedure in therapeutic practice.
Keywords: passive inclination; muscle thickness; transverse abdominal; external oblique; internal oblique